Weaving gender into sustainable intensification interventions - Fischer, Gundula (CAB International, 2022)
Sustainable intensification (SI) is understood as increasing productivity without causing harm to the environment. SI can be achieved by introducing more or different inputs (e.g., new knowledge and skills, labor, chemicals, and machinery); a change to higher-yielding crops or varieties, and more productive livestock breeds; a conversion to more productive farming systems (e.g., through irrigation); or a combination of these. This chapter introduces gender concepts in agricultural development and discusses the ways in which gender concerns can be woven into SI interventions to produce more equitable outcomes. Referring to Africa RISING experiences, the chapter describes activities that can enhance women's participation in SI, measure the benefits, and transform gender relations.